Evaluation of the teratogenicity of aqueous extract of labisia pumila var. alata in rats - Fuad, Wan Ezumi Mohd; Sulaiman, Siti Amrah; Islam, Mohamad Nazrul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2009)
A dose range study. to assess the teratogenic potential of aqueous extract of Labisia pumila var. alata (Kacip Fatimah) was conducted in rodents. The extract at doses of 0 (control), 2, 20, 200, 400, 1000 mglkglday were respectively administered by gavaging to 6 groups of pregnant Sprague Dawley rats from day 6 through day 16 of pregnancy and sacrificed on day 21. No significant agent-related effects including changes in maternal body weight (MBW) nor weight gain were observed. The corrected maternal body weights (CMBW) were slightly higher in animals receiving low dose extracts (2 mglkglday) as compared to all groups of animals. However, body weight differences were not statistically significant .. Gravid uterine weight, number of corpora lutea, number of implantation sites, percentage of foetal resorptlons, number of life foetuses, foetal weight and foetal sex ratio showed i10 significant differences among all group animals. None of the foetuses from all dams showed evidence of external congenital malformations. These findings may suggest that aqueous extracts ofLabisia pumila var. alata up to 1000 mglkglday ~tatlstically do not show any significant teratogenic effects In rats but do affect the maternal body weight and this is dose dependent